Peeling Away the Layers : Impacts of Durable Tariff Elimination - Gnutzmann-Mkrtchyan, Arevik (IMF Working Papers; Working Paper, 2018)
We demonstrate that durable MFN tariff elimination affects trade patterns through several layers, which generates non-linear impacts. First, complete tariff elimination results in a large additional trade gains over and above tariff reductions. Second, commitment to durable tariff elimination, through WTO bindings, further boosts both imports and exports of ITA members. The unique setting of the WTO Information Technology Agreement (ITA) allows us to identify these effects of non-discriminatory trade policies because (i) ITA constitutes a quasi-natural experiment as several 'passive' signatories joined it as an unavoidable part of pursuing of a larger policy objective, and (ii) ITA's partial coverage of the IT sector provides a natural control group for cross-product identification. Commitments under the ITA spurned development of a downstream IT export sector in 'passive' signatories.